Academic outlaws : queer theory and cultural studies in the academy - Tierney, William G. (Sage Publications, 1997)
Scholarly yet provocatively written, Academic Outlaws presents a comprehensive discussion of how life in academe is experienced by gay men and lesbian women. Using a narrative style that mixes autobiography, case study data, and fiction, author William G. Tierney provides timely insight into the challenges these people face in higher education and proposes an alternative process for redefining long-established cultural norms.